Design and Economic Optimization of Microgrid - Syed Mahaboob Shareef; Prasanth B. Venkata; Kumaraswamy I; Raju B. Sreenivasa; Ramya P. Sai; Rao Y. Ranga (E3S Web of Conferences)
In modern electrical systems, microgrids plays vital role in enhancing performance of the power system. The analysis uses HOMER tool for the simulation. Microgrids are small in ratings compared to the conventional energy sources and are independent power producers that can be more reliable and eco-friendly. HOMER helps to determine the proper combination of energy sources. The study considers the real time location of GUNTUR which is present in Andhra Pradesh state of INDIA. In the considered location to incorporate renewable energy sources in to the microgrid, the potential of wind and solar availability was estimated first. The simulation findings show that using HOMER microgrids use less non-renewable energy, work efficiently and with less operating cost to run. This gives an optimized solution for the sustained and smart power utilization.